SEROPREVALENCE OF TTI AMONG BLOOD DONORS AT THE BLOOD CENTER, LALITPUR: A RETROSPECTIVE CROSS-SECTIONAL STUDY - Jain, Priya; Kumar, Dharmendra; Tripathi, Amrita; Jain, Piyush; Singh, Shruti (Student’s Journal of Health Research Africa, 2025)
Background Millions of lives are saved by timely, safe, and enough transfusions; yet inappropriate transfusions raise the risk of transfusion-transmitted infections (TTIs) and cause numerous potentially fatal consequences. All infections that can spread from person to person by parenterally administering blood or blood products are known as TTIs. Objectives At a blood center at Autonomous State Medical College (ASMC), Lalitpur, Uttar Pradesh, the study sought to ascertain the TTI prevalence in both replacement and voluntary donors. Materials and Methods Data that were collected on donors of blood collected at a blood center between 2021 and 2024 was the subject of retrospective descriptive research. Data that were extracted from the database included age, sex, and donation type. The outcomes were total TTI, syphilis seropositivity, HIV, HBV, and HCV. Results The sociodemographic analysis revealed a predominantly male donor population (95.6%) with a mean age of 43.9±7.3 years, and the majority were family donors (81%). The overall seroprevalence of transfusion-transmitted infections (TTIs) was low, with Hepatitis B being the most prevalent at 0.48%, followed by HCV at 0.06%. No cases of HIV, syphilis, or malaria were detected. Year-wise distribution showed a non-significant variation in TTI seropositivity over the study period (p=0.24). Conclusion The study concludes that the prevalence of transfusion-transmitted infections is medium and has been declining over time. The most common infection is hepatitis B (HBsAg), which is followed by syphilis, HIV, and HCV. Recommendation Regular screening, stringent donor selection, and promotion of voluntary donations are recommended to further reduce the prevalence of transfusion-transmitted infections.